Meningkatkan Minat Belajar Literasi, Numerasi dan Pendidikan Karakter dengan Metode Groupwork - Viona Rosalinda Sembiring; Tuti Atika (Yayasan Literasi Sains Indonesia, 2023)
Education is an effort to prepare for the future. Learning is an absolute process that every human being undergoes. Interest in learning is important as a driver of learning. Interest in learning is an important factor in realizing quality education. Today, in Indonesia there are still many problems related to interest in learning. This of course must be a concern. In line with this, the purpose of this writing is to increase interest in learning by developing literacy, numeracy, and character education in students to be able to provide assistance in the midst of problems related to interest in learning. The location of the fieldwork practice carried out by the author is at UPT SDN 060902 Medan City Jln. Mangkubumi with a total of 19 students. This activity time lasts for 3 months. The method used in this study is the Groupwork method with stages (1) Assessment, (2) Planning, (3) Intervention, (4) Evaluation, and (5) Termination. The results of this activity show an increase in students' interest in learning. At the beginning of the meeting, the author found difficulties in increasing students' interest in learning but increasing in each meeting.